Effect of two erosive protocols using acidic beverages on the shear bond strength of orthodontic brackets to bovine enamel - Santos, Catielma Nascimento; Matos, Felipe De Souza; Rode, Sigmar De Mello; Cesar, Paulo Francisco; Nahsan, Flávia Pardo Salata; Paranhos, Luiz Renato (Dental Press International, 2018)
AbstractObjective:To assess the short-term effect of two in vitro erosive challenge protocols on the bond strength of metal orthodontic brackets on bovine enamel.Methods: Sixty bovine incisors were selected and randomly divided into six groups: AS7 (artificial saliva - 7 days, Control Group); CC7 (Coca-Cola™ - 7 days); LJ7 (lime juice - 7 days); AS30 (artificial saliva - 30 days, Control Group); CC30 (Coca-Cola™ - 30 days); LJ30 (lime juice - 30 days). Microhardness testing was performed prior to the erosive challenge to verify the standardization of samples. Immersion was performed 4x/day for five minutes, for either 7 or 30 days. After immersions were concluded, the brackets were bonded and shear bond strength was assessed after 48 hours. The Adhesive Remnant Index (ARI) was also assessed. Data were analyzed by two-way ANOVA, followed by Tukey’s post-hoc and Student’s t test for paired samples, and the Kruskal-Wallis non-parametric test (α = 5%).Results: The mean and standard deviation of microhardness testing of total samples were 281.89 ± 44.51 KHN. There was no statistically significant difference in shear bond strength for the time factor (7 or 30 days; F5.54= 0.105; p = 0.901). However, there was a statistically significant difference for the solution factor (F5.54= 6.671; p = 0.003). These differences occurred among solutions of Saliva x Coca-Cola™ (p = 0.003) and Coca-Cola™ x Lime Juice (p= 0.029). The assessment of the Adhesive Remnant Index showed no significant difference between groups.Conclusions: The immersion time used in the erosion protocols did not affect the bond strength of brackets to teeth. Coca-Cola™ induced significantly higher shear bond strength values than lime juice and artificial saliva. However, the short term effects of 7/30 days in this in vitro study may not be extrapolated for in vivo ones. Clinical studies should be conducted, substantiating the laboratory results.

ResumoObjetivo:avaliar o efeito de curto prazo de dois protocolos de desafio erosivo, in vitro, na resistência adesiva de braquetes ortodônticos metálicos em esmalte bovino.Métodos: Sessenta incisivos bovinos foram selecionados e divididos aleatoriamente em seis grupos: SA7 (saliva artificial - 7 dias, Grupo Controle); CC7 (Coca-Cola® - 7 dias); SL7 (suco de limão - 7 dias); SA30 (saliva artificial - 30 dias, Grupo Controle); CC30 (Coca-Cola® - 30 dias); SL30 (suco de limão - 30 dias). Foi realizado o teste de microdureza antes do desafio erosivo, para verificar a padronização das amostras. A imersão foi realizada quatro vezes ao dia, por cinco minutos, durante 7 ou 30 dias. Finalizadas as imersões, os braquetes foram colados e, após 48 horas, foi avaliada a resistência ao cisalhamento. O Índice de Adesivo Remanescente (IAR) também foi avaliado. Para análise dos dados, foram utilizados os testes ANOVA dois fatores, seguido do post-hoc de Tukey e teste t de Student para amostras pareadas, e o teste não-paramétrico de Kruskal-Wallis (α?#8197;= 5%).Resultados: a média e o desvio-padrão do teste de microdureza das amostras totais foi igual a 281,89 ± 44,51 KHN. Não houve diferença estatisticamente significativa na resistência ao cisalhamento para o fator tempo (7 ou 30 dias; F5,54= 0,105; p= 0,901). Contudo, houve diferença estatisticamente significativa para o fator solução (F5,54=6,671; p= 0,003). Essas diferenças ocorreram entre as soluções de Saliva x Coca-Cola® (p= 0,003) e Coca-Cola® x suco de limão (p= 0,029). Ao avaliar o Índice de Adesivo Remanescente, não foi possível verificar diferença significativa entre os grupos.Conclusões: o tempo de imersão utilizado nos protocolos de erosão não afetou a resistência de união dos braquetes aos dentes. A Coca-Cola® induziu valores de resistência ao cisalhamento significativamente mais altos do que o suco de limão e a saliva artificial. No entanto, os efeitos em curto prazo de 7 e 30 dias, nesse estudo in vitro, não podem ser extrapolados para os estudos in vivo. Estudos clínicos devem ser conduzidos, fundamentando os resultados laboratoriais.
Keywords: Erosion; Orthodontics; Orthodontic brackets; Shear strength.; Erosão; Ortodontia; Braquetes ortodônticos; Resistência ao cisalhamento.